PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID PADA MATA PELAJARAN INFORMATIKA KELAS X DKV DI SMK NEGERI 1 KOTO BARU (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to develop an Android-based interactive learning media for the Informatics subject for Grade X DKV students at SMK Negeri 1 Koto Baru. The research was motivated by the need for more innovative learning media, considering that most students already own Android smartphones, while their utilization in learning activities remains limited. The study employed a Research and Development (R&D) method using the ADDIE model, which consists of Analyze, Design, Development, Implementation, and Evaluation stages. The product was developed using Adobe Animate CC by integrating learning materials, animations, and interactive features. The feasibility of the media was evaluated through validation by material experts and media experts, as well as practicality testing by teachers and students. The validation results indicated that the media was categorized as valid, with an average score of 0.86 from material experts and 0.89 from media experts. The practicality test yielded scores of 90.67% from teachers and 86.80% from students, both classified as very practical. These findings suggest that the developed Android-based learning media is feasible, easy to use, and effective in supporting a more engaging and interactive Informatics learning process.